Audit Judgment dan Kegagalan Risiko Deteksi - Fitri Awaliyah; M. Nur A. Birton (Jurnal Akuntansi dan Governance, 2026)
Objectives: First, to identify and analyze the negative impacts of audit judgment based on four aspects of detection risk. Second, to classify these impacts into dharuriyyah, hajiyyah, and tahsiniyyah mafsadah to explain their urgency and ethical implications.Design/method/approach: The study adopts a qualitative, tawhid-based paradigm using semi-structured interviews with auditors from five public accounting firms. Data are analyzed through Braun and Clarke’s thematic analysis, with Ibn Ashur’s mafsadah serving as the primary interpretive framework.Results/findings: The analysis identifies thirteen core themes that shape audit risk detection. Limitations within these themes are shown to increase the likelihood of undetected material misstatements.Theoretical contribution: This study enriches the audit judgment literature by integrating Ibn Ashur’s mafsadah into detection risk analysis, framing audit failure as not only a technical issue but also an ethical and social problem with systemic implications.Practical contribution: The findings highlight the need to strengthen technical competence, audit procedures, sampling, and the assessment of financial reporting complexity to enhance detection risk. These insights are relevant for audit firms, regulators, and professional bodies in formulating standards-compliant policies that safeguard the public.Limitations: The qualitative scope and limited number of informants constrain generalizability, the use of Ibn Ashur’s mafsadah entails interpretive subjectivity.